Risk factors for early discontinuation of breastfeeding before two years age - Bibi, Saima; Gilani, Syed Yasir Hussain; Bibi, Sadia (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the risk factors regarding early cessation of breastfeeding. Method: The cross-sectional study was conducted at the Paediatrics Department of Ayub Medical Teaching Institute, Abbottabad, Pakistan, from June 2022 to February 2023, and comprised mother-child dyads who initiated the breastfeeding process at birth, but failed to continue over the subsequent 24 months. Data was collected using a structured proforma through interviews with mothers. Data was analysed using SPSS 26. Results: There were 250 mothers with mean age 28.48±5.73 years, while the mean age of 250 children was 14.64±7.53 months. The mean duration of breastfeeding was 5.05±3.99 months. The major risk factors identified were a combination of breastfeed and bottle-feed in the first month of life in 198(79.2%) cases, maternal diet restriction postpartum 186(74.4%) and no counselling about breastfeeding 168(67.2%). Pacifier use (p= 0.002), combined bottle-feed and breastfeed in the first month of life (p=0.001) and mothers wrongly considering formula milk healthier than breastfeed (p=0.000) were significant predictors of shorter duration of breastfeeding. Conclusion: All the reasons identified as potential risk factors for early discontinuation of breastfeeding were modifiable. Health education-based interventions are needed for optimising breastfeeding practices. Key Words: Cessation of breastfeeding, Exclusive breastfeeding, Breastfeeding duration.